Key thinkers on cities - Koch, Regan; Latham, Alan (SAGE, 2017)
Key Thinkers on Cities provides an engaging introduction to the dynamic intellectual field of urban studies. It profiles the work of 40 innovative thinkers who represent the broad reach of contemporary urban scholarship and whose ideas have shaped the way cities around the world are understood, researched, debated and acted upon. Providing a synoptic overview that spans a wide range of academic and professional disciplines, theoretical perspectives and methodological approaches, the entry for each key thinker comprises: A succinct introduction and overview ; Intellectual biography and research focus ; An explication of key ideas ; Contributions to urban studies.